Determinants Of Employee Satisfaction: A Survey Of Healthcare Workers Of A Group Of Hospitals In Karachi - Muhammad Ahmar Jamal; Anoop Dawani; Syed Hasan Danish; Minhaj Qidwai; Farah Ahmad (ziauddin University, 2024)
Background: To assess the satisfaction levels of employees in a health care organization at Karachi, Pakistan. Methods: A cross sectional survey was conducted on 598 employees working at University and tertiary care hospital for a period of 5 months. Purposive sampling technique was used for collection of data. All employees working for at least one year at any level of management were included in the study. Part time employees, visiting staff, those absent at the time of data collection and those who refused to consent were excluded from the study. Self administered questionnaires were utilized for the purpose of data collection. Entire analysis was performed using SPSS version 20. P value less than 0.05 was taken as significant. For descriptive statistics frequency and percentages were calculated for categorical variables while mean and standard deviation for numerical variables. Analysis of Variance was applied to see association between different groups. The study was approved by the ethical review board. Results: Majority 69.4% (n=415) employees were found to be satisfied. Upper management was seen to have slightly lower scores of satisfaction compared to middle and lower management levels. Between clinical & non-clinical side there was also no significant difference observed in the satisfaction level. Satisfaction levels were seen directly proportional to age and length of service. When overall benefits were seen non clinical side 61% (n=84) were found to be more dissatisfied than clinical side 40% (n=53). Conclusion: Study findings conclude that majority employees were satisfied. However most were dissatisfied with the overall benefit package and vacation policy. Key Words: Employee satisfaction, Management, Tertiary care hospital